THE INFLUENCE OF MANAGERIAL SKILLS ON THE SUCCESS OF YOUNG ENTREPRENEURS IN THE DIGITAL ERA MEDIATED BY BUSINESS NETWORKS - Titin Dunggio; Meylani Airmas; Putri Adtirah Tumampas; Cindrawati H. Karim (LP2M Universitas Bina Mandiri Gorontalo, 2025)
The growing of young entrepreneurs in the digital era reflects a new dynamic in the entrepreneurial landscape, particularly with the rise of digital transformation that has reshaped how businesses operate. However, behind this growth, many young entrepreneurs face challenges in managing their ventures effectively. This study aims to analyze the influence of managerial skills on the success of young entrepreneurs in the digital era, by considering the mediating role of business networks. A quantitative approach was applied using a sample of 52 MSME actors. The data were analyzed using Partial Least Square Structural Equation Modeling (SEM-PLS). The results show that managerial skills have no direct significant effect on business success (T-statistic = 0.127; P-value = 0.899). However, managerial skills significantly influence business success through the mediation of business networks (T-statistic = 5.207; P-value = 0.000). These findings highlight the crucial role of digital business networks as a bridge between managerial competencies and business performance. The study provides essential implications for digital entrepreneurship development programs that emphasize the synergy between managerial skills and networking strategies.